The Role of Informed Consent in High-Risk Dental Procedures as Reviewed under Law No. 17 of 2023 on Health - Intan Yumanita; Redyanto Sidi; Marice Simarmata (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study examines the legal role of informed consent in high-risk dental medical procedures under Law Number 17 of 2023 on Health. Informed consent represents not only an ethical obligation but also a legal mechanism ensuring patient autonomy and professional accountability. Using a normative juridical method with statutory, conceptual, and case approaches, this research analyzes how the new legal framework strengthens patient protection and defines the professional responsibilities of dental practitioners. The findings indicate that despite the law’s explicit provisions particularly Articles 293 and 294 implementation remains constrained by limited legal literacy, ineffective communication, and insufficient documentation among practitioners. From the ethical perspective, informed consent reflects respect for autonomy, while legally it serves as preventive protection against malpractice claims. Therefore, enhancing professional understanding, integrating bioethics and health law in education, and ensuring standardized consent documentation are essential to achieving transparent, fair, and patient-centered dental services in Indonesia.